Spectroelectrochemical study on catecholase catalytic activity of selected mononuclear copper(II) complexes - Kocábová, Jana; Sýs, Milan; Klikarová, Jitka; Novák, Miroslav; Bártová, Michaela; Jirásko, Robert; Hana, Tarábková; Sokolová, Romana; Mikysek, Tomáš (My University, 2023)
The catecholase activity of selected mononuclear copper(II) complexes with two different types of pyridylmethylamine ligands (L1, L2) and in combination with copper(II) salts (chloride and perchlorate ligands), towards polyphenols has been studied in aqueous and nonaqueous media. The presence of the electron-rich (methoxy) substituents in the ligand (L2) and perchlorate ligand have significantly increased the catalytic efficiency (kcat/Km) from 4.1 to 45.2 (s−1 µmol−1 L) towards 3,5-di‑tert-butylcatechol. There were observed marked changes in the IR absorption spectrum during the chemical reaction of 3,5-di-tert-butylcatechol with oxygen catalysed by 4 [CuL2)](ClO4)2. The IR spectroelectrochemistry served as a unique tool for defining the mode of catalysis action via the control potential applied during reaction. The UV-Vis spectroelectrochemical study has proved that all mononuclear copper(II) complexes show a quasi-reversible electron transfer (Cu2+/Cu+ redox couple) and compound 4 is able to reversibly catalyze the oxidation of catecholamines to the corresponding polyindoles even in aqueous media. The results presented emphasized the choice of anionic ligand, character of Cu-N coordination bonds, together with chemical stability are all the key factors for a modeling of new biomimetic copper(II) complexes for the development of specific analytical devices with a long-life service.
Spektroelektrochemické studium katecholázové katalytické aktivity vybraných mononukleárních měďnatých komplexů
Keywords: Mononuclear copper(II) complexes; tyrosinase biomimetic catalyst; catecholase-like activity; IR spectroelectrochemistry; neurotransmitters; Mononukleární komplexy mědi(II); tyrosinázový biomimetický katalyzátor; aktivita podobná katecholáze; IR spektroelektrochemie; neurotransmitery